Multi-isotope Dietary Reconstruction of Modern and Beringian Gray Wolves - Lindroos, Eve (Université d'Ottawa | University of Ottawa, 2025)
Understanding how species adapt to environmental change is critical as many species are threatened by extinction under ongoing climate change. Beringia, the land mass that connected Yukon and Alaska with eastern Siberia throughout much of the Late Pleistocene (~115,000 to 11,700 years before present [BP]), experienced significant climatic warming during the terminal Pleistocene (~16,000−11,700 BP) and the increasing presence of humans in North America (~24,000−12,000 BP), both being coincident with a widespread North American megafaunal extinction event. However, species like the gray wolf (Canis lupus) survived, possibly due to dietary flexibility. I am revisiting this hypothesis by combining existing and novel palaeodietary proxies. Stable isotopes in animal tissues reflect the consumers' diet, making them a powerful tool for dietary reconstructions of modern and extinct species. Carbon (δ¹³C) and nitrogen (δ¹⁵N) isotopes are commonly used in palaeodietary studies but are vulnerable to the degradation of organic molecules and to environmental baseline shifts. Calcium isotopes (δ⁴⁴/⁴²Ca), Sr/Ca, and Ba/Ca have been proposed as a complementary and potentially more robust dietary proxies. I radiocarbon dated and analyzed δ¹³C, δ¹⁵N, δ⁴⁴/⁴²Ca, Sr/Ca, and Ba/Ca in the remains (bone and tooth enamel) of modern and Pleistocene wolves (n=15 and n=14, respectively) and their potential modern and Pleistocene prey species (n=20 and n=22, respectively). Using Bayesian stable isotope mixing models (BSIMMs), I reconstructed gray wolves’ prey preferences and dietary habits over the past 50,000 years. As expected, BSIMMs relying on δ¹³C and δ¹⁵N data showed that Pleistocene wolves primarily consumed large ungulates, with pre-LGM and LGM wolves having a horse-specialized diet whereas modern wolves had a more generalist diet. When the δ⁴⁴/⁴²Ca values were added as a third dimension, BSIMMs showed evidence of an even greater dietary shift with Pleistocene wolves consuming almost exclusively horses, whereas modern wolves showed a more diverse and small prey (i.e., snowshoe hare and arctic ground squirrel) dominated diet. Calcium isotopes reinforce the hypothesis that Pleistocene wolves adapted to deglaciation and the extinction of Beringian horses during the terminal Pleistocene by shifting to a more generalist and flexible diet focusing on small prey and other large ungulates. This study provides key information on the palaeoecology of Beringian mammals and underlines the importance of diet in biodiversity conservation, which can help inform effective management strategies for at-risk species in the face of current and future climate change. Besides the palaeoecological insights, my work also demonstrates a key methodological advance with the addition of calcium isotopes as a third, more robust palaeodietary dimension less influenced by environmental baselines and diagenesis. This offers an intriguing glimpse into the relatively unexplored potential of calcium isotopes to further investigate palaeodiets of animals and presents an exciting development in the integration of traditional (i.e., carbon and nitrogen) and non-traditional (i.e., calcium) isotope geochemistry into the field of palaeobiology.
Keywords: Stable isotopes; Calcium isotopes; Sr/Ca; Ba/Ca; Dietary ecology; Novel dietary proxies; Traditional dietary proxies; Gray wolf; Beringia